Peran Orangtua Penambang Emas Dalam Menanamkan Pendidikan Agama Islam Pada Anak Dikelurahan Kampung Jawa - Asri Karolina; Wilyam Afsiska; Beni Azwar; Cikdin Cikdin; Eka Yanuarti (STAI Bumi Silampari, 2020)
The purpose of this study is to describe the condition of Islamic religious education in children of gold miners in the Kampung Jawa Village, find out the role of parents in instilling Islamic religious education especially moral education in their children, helping the problematic role of parents in instilling Islamic religious education in particular moral education in children in Kampung Jawa Village. This type of research is qualitative research. The type of data used in this study are primary and secondary data. The subjects in this study were the village chief, religious leaders and gold miner parents. Data collection techniques are structured interviews, observation and documentation. The final step is drawing conclusions and verification. Based on the results of the study show that: first, the condition of Islamic religious education in the children of gold miners in the Kampung Jawa Village, namely religious understanding can be quite good. Second, the role of parents of gold miners in instilling moral education to their children varies depending on the understanding of parental religious knowledge. Third, the probelmatic role of parents consists of internal factors that are constrained by parents who are busy working that make children less controlled to behave properly according to Islamic teachings, external factors that are constrained by children unruly and difficult to be advised.